Solvent production from palm oil mill effluent (POME) by clostridium beijerinckii - Ma Umaira Suhaddha, Zainal Abidin (2012)
Acetone,butanol and ethanol have widely been used in many industries.butanol and ethanol have been recognize as potential biofuel.While acetone is important as fuel tracer in field of combustion and use as suspension agent in pharmaceutical preparation.In 1990s,the increasing price of sugarcane have increased the production cost of ABE fermentation and the only factor that causing ABE fermentation could not survive was due to the cost of raw materials of substrate By using POME as substrate for fermentation process of acetone,butanol and ethanol(ABE), production is at advantage due to its lower cost and readily available.This study is to determine the effect of concentration of substrate,modified glucose concentration on substrate and initial pH of substrate towards enhancing solvent production from palm oil mill effluent(POME) by Clostridium beijerinckii.The experiment has been carried out in a batch culture system.The study of substrate pH effect ranged from 4.7, 5.2, 5.7 to 6.2.Meanwhile, for study of substrate concentration ranged from 60%,70%,80%,90% to 100%. The study of modified substrate concentration effect were ranging from 20g/L,30g/L,40g/L,50g/L to 60g/L.The fermentation of POME which produced acetone,butanol and ethanol,was analysed using gas chromatography flame ionization detector(GC-FID)and isobutanol was used as the internal standard.The experiment was using one factor at one time (OFAT) method to determine the best range values.From the parameters stated,sedimented POME at 70% concentration with initial pH increased to 5.7 is most suitable for solvent production 70% with 1.025g/L solvent produced.While 50g/L is the optimal concentration of modified glucose that enhanced the solvent production with supported by operating temperature at 37°c and 150rpm which 1.241g/L solvent produced.Apart from that,growth cell at pH5.7 maximize the solvent production where 0.967g/L solvent produced.In addition,DNS test for glucose consumption of all parameters studies can be conclude that higher glucose consumption resulted in higher amount of total solvent produced.The results obtained from these experiments showed that POME could be a viable media for ABE fermentation.